Pengaruh People Pleaser terhadap Kesehatan Mental dan Hubungan Sosial pada Remaja - Marianti, Lena; Mawaddah, Nabillah Nurul; Kusuma, Tiara; Nufus, Hayatun; Khodijah, Siti; Syahlan, Muhammad (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2026)
People pleaser behavior increasingly prevalent among adolescents due to social pressures and digital media poses risks to mental health and interpersonal relationships. This study aims to analyze the impact of people pleaser tendencies on adolescents' psychological well-being and social relations through qualitative Systematic Literature Review (SLR). Population comprised relevant scientific literature from 2016-2025, with purposive sample of 20-30 sources from Google Scholar, ScienceDirect, and JSTOR. Instruments involved structured keyword searches followed by thematic coding and narrative synthesis analysis. Results reveal strong correlations between people pleaser traits and elevated stress, anxiety, low self-esteem, alongside imbalanced relationships due to poor personal boundary setting. Conclusions recommend assertiveness training and REBT interventions to enhance adolescent well-being, offering practical implications for school counselors.